Clinical InvestigationsLong term results of PDR brachytherapy for lip cancer - Johansson, Bengt; Karlsson, Leif; Hardell, Lennart; Persliden, Jan (Journal of Contemporary Brachytherapy, 2011)
Purpose : To evaluate the long time outcome with regard to local tumour control and side effects of a pulsed dose rate (PDR) monobrachytherapy of primary or recurrent cancer of the lip. Material and methods : Between 1995 and 2007 we treated 43 patients with primary or recurrent clinical T1-T3N0 lip cancers. There were 22 T1 patients (51%), 16 T2 (37%) and 5 T3 cases (12%). A median dose of 60 (55-66) Gy was given, depending on the tumour volume. The PDR treatment was delivered with 0.83 Gy/pulse every second hour for 5.5-6.5 days. The patients were followed for a median of 55 (1-158) months. Results : The 2-, 5- and 10-year rates of actuarial local control were 97.6%, 94.5% and 94.5%, overall survival 88.0%, 58.9% and 39.1%, disease free survival 92.7%, 86.4% and 86.4% respectively. The regional control rate was 93%. One patient (2%) developed distant metastases. A dosimetrical analysis showed a mean treated volume of 14.9 (3.0-56.2) cm 3 . Long-term side effects were mild and the cosmetic outcome excellent, except for 1 case (2%) of soft tissue necrosis and 1 case (2%) of osteoradionecrosis. Conclusions : Local outcome is excellent and similar to other published studies of continuous low dose rate (cLDR) brachytherapy.